(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The scientific and applied achievements of Institute of the Chemistry of Plant Substances (ICPS) on the development of products for agriculture for the last years are summarized. Also included different research areas, working to find new promising drugs based on natural, heterocyclic compounds and their synthetic analogues. In this mini review many preparations: plant growth regulators, fungicides, herbicides, which are created in ICPS and recommended for application in agriculture, have been discussed.